Interception of values as a result of the business model restructuring – case study - Nogalski Bogdan; Niewiadomski Przemysław (Management, 2017)
The main objective of this paper is to present a case of value interception as a result of restructuring the business model of a manufacturing company that operates in the agricultural machinery sector. A company that focuses on core activities in the value chain and commissions the manufacturing of most components to specialised suppliers – as a result of restructuring – becomes an integrator that controls all parts of the supply chain; from obtaining a raw material, through its own production of a possibly large number of components, to the distribution of a finished composite product. The framework of the conducted research featured the identification of the relationships occurring between own production of components comprising a given product, and an alternative solution, i.e. possibility of acquiring them by way of co-operation. The authors assumed that a derivative of the value intercepted in the finished product implementation process is the number of components manufactured using own production resources.